ISLAMIZATION OF CONTEMPORARY ARCHITECTURE: SHIFTING THE PARADIGM OF ISLAMIC ARCHITECTURE - Hamouche, Mustapha Ben- (Journal of Islamic Architecture, 2010)
Islamic architecture is often thought as a history course and thus finds its material limited to the cataloguing and studying of legacies of successive empires or various geographic regions of the Islamic world. In practice, adherent professionals tend to reproduce high styles such as Umayyad, Abassid, Fatimid, Ottoman, etc., or recycle well known elements such as the minarets, courtyards, and mashrabiyyahs. This approach, endorsed by the present comprehensive Islamic revival, is believed to be the way to defend and revitalize the identity of Muslim societies that was initially affected by colonization and now is being offended by globalization. However, this approach often clashes with the contemporary trends in architecture that do not necessarily oppose the essence of Islamic architecture. Furthermore, it sometimes lead to an erroneous belief that consists of relating a priori forms to Islam and that clashes with the timeless and universal character of the Islamic religion. The key question to be asked then is, beyond this historicist view, what would be an â€œIslamic architec-tureâ€ of nowadays that originates from the essence of Islam and that responds to contemporary conditions, needs, aspirations of present Muslim societies and individuals. To what extends can Islamic architecture bene-fits from modern progress and contemporary thought in resurrecting itself without loosing its essence. The hypothesis of the study is that, just as early Muslim architecture started from the adoption, use and re-use of early pre-Islamic architectures before reaching originality, this process, called Islamization, could also take place nowadays with the contemporary thought that is mostly developed in Western and non-Islamic environ-ments. Mechanisms in Islam that allowed the â€œabsorptionâ€ of pre-existing civilizations should thus structure the islamization approach and serve the scholars and professionals to reach the new Islamic architecture. The objectives of the paper consist of counter-criticizing orientalistsâ€™ views that overwhelm our libraries and references systems, and that consider the first stage of Islamic civilization, within which architecture is part, as a mere cut-and-paste process and, at best, a synthesis of these pre-Islamic heritages, and overcoming the prevailing historicist approach, and open new scopes for future generations to instate a new era of islamization that permits digesting the contemporary Western thoughts in a conscious, critical, and constructive way.